1988
DOI: 10.1016/0143-4179(88)90060-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of β-endorphin-immunoreactivity in limbic brain structures of rats self-administering heroin or cocaine

Abstract: Abstract-The effects of intravenous self-administration of 3Opg infusions of either heroin or cocaine, or saline on the concentrations of f3-endorphin-immunoreactivity (BE-IR) in the anterior part of the rat brain limbic system were studied. Self-administration of heroin and cocaine for 5 daily sessions resulted in a marked reduction of the concentrations of BE-IF? in the nucleus accumbens, rostra1 striatum, septum and hippocampus at the time of the scheduled next session on day 6. In pooled extracts of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Indeed, we found a Pomc mRNA downregulation both in the dorsal and ventral striatum in cocaine-exposed compared to yoked-saline rats, irrespective of Strain. Similar evidence was reported by Sweep et al (1988) showing that rats self-administering heroin or cocaine have decreased amounts of beta-endorphin in DS and NAcc, measured by high-pressure liquid chromatography, compared to saline rats. However, another report showed higher release of the peptide in the NAcc of rats exposed to cocaine self-administration compared to saline-control rats using microdialysis and ELISA assays (Roth-Deri et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, we found a Pomc mRNA downregulation both in the dorsal and ventral striatum in cocaine-exposed compared to yoked-saline rats, irrespective of Strain. Similar evidence was reported by Sweep et al (1988) showing that rats self-administering heroin or cocaine have decreased amounts of beta-endorphin in DS and NAcc, measured by high-pressure liquid chromatography, compared to saline rats. However, another report showed higher release of the peptide in the NAcc of rats exposed to cocaine self-administration compared to saline-control rats using microdialysis and ELISA assays (Roth-Deri et al, 2003).…”
Section: Discussionsupporting
confidence: 87%
“…β-EP, one of the most important endogenous opioid peptides, is distributed widely in the central nervous system and is responsible for a wide range of biological activities in the body (He et , 2011;Maslov et al, 2013;Wang et al, 2006). Our results demonstrated that chronic heroin resulted in a significant reduction of β-EP in the mPFC and AcbC within the corticolimbic system, which is consistent with the previous studies (Sweep et al, 1988(Sweep et al, , 1989. Interestingly, heroin-induced neuronal apoptosis were also detected in the mPFC and AcbC, and HP treatment normalized the β-EP levels and neuronal morphologies in the same areas.…”
Section: Discussionsupporting
confidence: 95%
“…In rats engaging in morphine-seeking behavior (prior to any infusion of morphine), changes occur in monoamine and amino acid neurotransmitter turnover rates in the NAc, hippocampal formation, septum, amygdala, and the brainstem, relative to those seen in morphine-yoked controls (Smith et al 1984). Furthermore, at the regularly scheduled time of self-administration, decreases are observed in β-endorphin immunoreactivity in limbic structures, including the NAc, septum, hippocampus, and rostral striatum, that are suggestive of a conditioned decrease in β-endorphin turnover (Sweep et al 1988;Sweep et al 1989). Based on these findings, it can be postulated that the BLA may mediate incentive motivational effects of heroin and heroin-paired conditioned stimuli through its interaction with selective cortical structures and the mesocorticolimbic dopamine system.…”
Section: Discussionmentioning
confidence: 86%